Leucocytes and Th-associated Cytokine Profile of HIV-Leishmaniasis Co-Infected Persons Attending Abuja Teaching Hospital, Nigeria - Abdullahi, Idris Nasir (Eurasian J Med, 2020)
OBJECTIVE: T-helper cells (Th)-1& -2 cytokines homeostasis control or predict clinical outcome of infected persons, especially those with HIV /AIDS. This case-control study evaluated the leucocytes differentials, TNF-alpha, interleukin (IL)-2 and -10 levels among HIV infected persons with serological evidence of leishmaniasis attending University of Abuja Teaching Hospital, Nigeria MATERIALS AND METHODS: Blood samples from 28 HIV infected persons who had Leishmania donovani rK39 and Immunoglobulin-G (IgG) positive (group 1), 30 age- & -sex matched HIV infected persons without Leishmania antibodies (group 2) and 30 apparently healthy persons without HIV and Leishmania antibodies (group 3). Full blood counts, TNF alpha, IL-2 and -10 levels were analyzed using automated hematology analyzer and ELISA, respectively. Structured questionnaires were used to collate biodata and clinical presentations of participants. RESULTS: Ten (35.7%) participants in group 1 were on ART, 15 (50%) in group 2 were on ART, while group 3 were ART naïve. There were significantly higher values in basophil (4.4±2.5%) and eosinophil counts (12.9±3.8%) in HIV/leishmania coinfected persons (p<0.005). However, other white cells subpopulation was significantly lower in HIV/leishmania co-infected participants (p<0.05). There was significantly reduced CD4+ T cell counts ([119±26 versus 348±63 versus 605±116 cells/mm3]), TNF-alpha ([36.82±8.21 versus 64.67±12.54 versus 254.98±65.59 pg/mL]) and IL-2 levels ([142.14±20.91 versus 507.6±84.42 versus 486.62±167.87 pg/mL]) among HIV/Leishmania co-infected participants compared to group 2 and group 3 participants, respectively. However, higher IL-10 level (80.35±14.57 pg/mL) was found in HIV/Leishmania co-infected participants as opposed to the HIV monoinfected (62.2±10.43 pg/mL) and apparently healthy persons (23.97±4.88 pg/mL) (p<0.001). CONCLUSION: Eosinophil, basophil counts and serum IL-10 level were high in HIV/Leishmania coinfected persons, demonstrating parasite-induced hypersensitivity and immunosuppression.